Évolution du portrait littéracique d'élèves inscrits à la maternelle de l'école Wahta' à Wendake - Picard, Alexandra (Université Laval, 2020)
This research presents the evolution of the literacy of 11 kindergarten children at Wahta’ school, an elementary school located in the community of Wendake, in Québec. Two data collections were carried out: one at the beginning of the school year and the other at the end of the 2018-2019 school year. These data collections made it possible to determine the children's reading and writing skills. In order to assess their progress, three foundations were analyzed: the narration, the syntax and the representation of the alphabetical system. The results show that the majority of children make progress in structuring the narrative, but few achieve the level of causality necessary at the start of formal learning to read. In terms of syntax, qualitative analyzes show little progress, as children from the start of the year are generally already advanced. As for the representation of the alphabetical system, more than half of the children did not progress at the code level. At the end of kindergarten, only five children out of eleven show sufficient progress to the beginnings of decoding. This study highlights the importance of monitoring the literacy development of First Nations children and of fostering the emergence of literacy by anchoring it in interventions involving culture and child's literature of First Nations. Le présent projet de recherche présente l’évolution du portrait littéracique de 11 élèves de maternelle inscrits à l’école Wahta’, une école primaire située dans la communauté de Wendake, à Québec. Deux collectes de données ont été réalisées : une au début de l’année scolaire et l’autre à la fin de l’année scolaire 2018-2019. Ces collectes de données ont permis de déterminer les habiletés des enfants en lecture et en écriture. Afin d’évaluer leur progression, trois fondements ont été analysés auprès des élèves : la structuration du récit, la structuration de la syntaxe et la représentation du système alphabétique. Les résultats montrent que la majorité des enfants progressent concernant la structuration ...